Mechanistic studies of the impact of chronic pain on brain, behaviour and cognition in a rodent model of chemically induced osteoarthritis - Gonçalves, Sara V (2021)
Chronic pain has been associated with changes in forebrain regions, including the hippocampus and prefrontal cortex, and impairments in cognitive functions associated with these forebrain regions, including impairments in memory and cognitive flexibility. Osteoarthritis (OA) is a major public health burden, and the main symptom of OA is chronic pain. The impact of OA pain on cognitive function is poorly understood. By combining methods from pain research and behavioural integrative neuroscience, in this PhD work, the impact of OA-like chronic knee pain on selected cognitive functions was investigated in a well-characterised rodent model.